Adherence to the 2012 European gonorrhoea guideline in the WHO European Region according to the 2018–19 International Union against Sexually Transmitted Infections European Collaborative Clinical Group gonorrhoea survey. (January 2020) - Unemo, M; Clarke, E; Boiko, I; Patel, C; Patel, R
Gonorrhoea is a major public health problem globally. Increasing incidence in many particularly developed countries and the emergence of resistance to the extended-spectrum cephalosporin ceftriaxone, the last option for empiric first-line monotherapy, are of serious concern. This paper evaluates the results of the 2018–19 International Union against Sexually Transmitted Infections European Collaborative Clinical Group survey on the diagnosis and treatment of gonorrhoea in Europe. Although high quality clinical care was reported in many European settings, in several countries the testing, diagnostics, antimicrobial treatment, and follow-up of gonorrhoea patients were evidently suboptimal. Increased adherence to evidence-based European and/or nationally-adapted management guidelines is essential in controlling the increasing incidence of gonorrhoea in many European settings and the spread of ceftriaxone-resistant, multidrug-resistant, and extensively drug-resistant gonorrhoea.